Brief overdose education can significantly increase accurate recognition of opioid overdose among heroin users - Jones, Jermaine D. (2013)
BACKGROUND: In an effort to increase effective intervention following opioid overdose, the New York State Department of Health (NYSDOH) has implemented programs where bystanders are given brief education in recognizing the signs of opioid overdose and how to provide intervention, including the use of naloxone. The current study sought to assess the ability of NYSDOH training to increase accurate identification of opioid and non-opioid overdose, and naloxone use among heroin users. METHODS: Eighty-four participants completed a test on overdose knowledge comprised of 16 putative overdose scenarios. Forty-four individuals completed the questionnaire immediately prior to and following standard overdose prevention training. A control group (n =40), who opted out of training, completed the questionnaire just once. RESULTS: Overdose training significantly increased participants’ ability to accurately identify opioid overdose (p<0.05), and scenarios where naloxone administration was indicated (p<0.05). Training did not alter recognition of non-opioid overdose or non-overdose situations where naloxone should not be administered. CONCLUSIONS: The data indicate that overdose prevention training improves participants’ knowledge of opioid overdose and naloxone use, but naloxone may be administered in some situations where it is not warranted. Training curriculum could be improved by teaching individuals to recognize symptoms of non-opioid drug over-intoxication.